Diskursus Ulama Seputar Penafsiran Al-Qur’an Tentang Memilih Kepala Daerah Non-Muslim Di Indonesia - Faizin, Afwan; Bahary, Ansor; Sa'dijah, Chalimatus (MISYKAT: Jurnal Ilmu-ilmu Al-Quran Hadist Syari'ah dan Tarbiyah, 2023)
This article proves that the interpretation of the Koran is greatly influenced by the socio-political background of the interpreter which influences their interpretation and the choice of approach they use. The regional head election (Pilkada) contest in DKI Jakarta is an arena for seeking the legitimacy of each interpreter for the intent of Qs. al-Ma'idah: 51. On the other hand, a textual approach based on a linguistic approach (al-'ibrah bi' general al-lafdzi) gave birth to an exclusive interpretation in rejecting non-Muslim Regional Head candidates. Meanwhile, the basis of the socio-historical approach ('al-ibrah bi especially al-sabab) is a more inclusive religious foundation that allows non-Muslim Regional Head candidates. The choice of this approach seems to have a reciprocal correlation with the socio-political setting of the interpreter, because in fact the interpretation of awliya' in Qs. Al-Maidah: 51, is neutral. Etymologically it can be interpreted; close, friend, protector, helper, leader, alliance, ally, intimate, lover, soul mate and maybe many more. However, when scholars have a certain tendency, in the end the interpretation of awliya' is brought to the subjective meaning of the interpreter, even though the interpreter claims to have constructed an interpretation that is objective and universal in nature. This research is a field research with a hermeneutic approach. Sources of data are Muslim scholars who are experts in the field of interpretation of the Koran from various backgrounds by purposive sampling according to the expertise of the informants.